Investigating the role of pain‐modulating pathway genes in musculoskeletal pain. (21st June 2012) - Holliday, K.L.; McBeth, J.; Macfarlane, G.; Huhtaniemi, I.T.; Bartfai, G.; Casanueva, F.F.; Forti, G.; Kula, K.; Punab, M.; Vanderschueren, D.; Wu, F.C.; Thomson, W.
Abstract Aims The aim of this study was to determine if genetic variation in the pain‐modulating gene DREAM and its pathway genes influence susceptibility to reporting musculoskeletal pain in the population. Methods Pairwise tag single nucleotide polymorphisms (SNPs) in DREAM, PDYN and OPRK1 were genotyped in a UK population‐based discovery cohort in whom pain was assessed using blank body manikins at three time points. Depression and anxiety symptoms were assessed at the first time point. Zero‐inflated negative binomial regression was used to test for association between SNPs and the maximum number of pain sites reported (0–29) across the three time points. Significantly associated SNPs (p < 0.05) were subsequently genotyped for validation in a cohort of European men with pain assessed at two time points. Results Thirty‐five SNPs were genotyped in 1055 subjects, of whom 83% reported pain, in the discovery cohort. SNPs in each gene were associated with the maximum number of pain sites reported, were independent of symptoms of anxiety and depression and had a significant cumulative effect (p = 7.0 × 10−5). Significantly associated SNPs were successfully genotyped in 1733 men, 76% of whom reported pain, in the validation cohort, but did not show significant association with the number of pain sites. Conclusions Genetic variation in the DREAM pathway genes was associated with the extent of pain reporting in a population‐based cohort. These findings were not replicated in a single independent cohort; however, given the potential of this pathway as a therapeutic target, further investigation in additional cohorts is warranted.